Determinan Dual Form of Malnutrition pada Ibu dan Anak di Indonesia: Studi Literatur. - Pangestuti, Meitriana; Dewi, Kifayati Rosiyanti (Universitas Muhadi Setiabudi, 2025)
Double burden of malnutrition not only coincide at the population levels, but can occurs in the same household. This incidence can occur as Dual Form of Malnutrition (DFM) shown by presence of stunted children and maternal overweight/obese in the same time. DFM has more significant effect on child and maternal health status, productivity and economic problems. This study aims to find out determinant DFM in Indonesia. The method used in this study was literature review research using Google Scholar and Pubmed with inclusion and exclusion criteria. Result of review presented in narrative writing. There are 3 articles matched with criteria. Determinant for DFM in Indonesia by presence child stunting and maternal overweight/obese are paternal and maternal education, household income, maternal occupation, parity, maternal height, responsive feeding, breastfeeding history, protein intake of the children, and fat intake of the mother. Determinant for DFM are direct causes in the form of socio-demographic factors and dietary patterns, and indirect causes in the form nutrition intake of children and mother.